The proprieties and metabolism of osseous tissue - Łysoń-Wojciechowska, Grażyna (Anthropological Review, 1976)
The metabolism of osseous tissue in phisiological states exhibits quantitative as well as qualitative differences conditioned by the relationship between restitutive, reconstructive and resorption processes. The predominance of one of those processes over the others is decisive for the functional state of the osscous tissue, at a given time and depends on many factors of u humoral and hormonal nature. The influence of some endogenic factors on the osseous tissue. with particular consideration of the control of calcium metabolism of the organism, is reported.